Pengaruh investasi dalam negeri luar negeri dan pengeluaran pemerintah di bidang kesehatan terhadap pertumbuhan ekonomi di Provinsi Bengkulu: Pengaruh investasi dalam negeri luar negeri dan pengeluaran pemerintah di bidang kesehatan terhadap pertumbuhan ekonomi di Provinsi Bengkulu - dela aura merisca (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
An economy is good if the current level of economic activity is higher than what was achieved before. Foreign direct investment (PMA) and domestic investment (PMDN) are important sources of financing for developing regions and are capable of making a sizeable contribution to development. Government expenditure itself is a tool for government investment in the economy which is considered the most effective. Investment in the country, abroad and expenditure in the health sector in Bengkulu province has increased but Bengkulu province itself has a GRDP which has decreased no. economy in Bengkulu province. The analytical method used in this study is a quantitative method using multiple linear regression. The writing of this research was carried out using time series data. The data collection technique used was secondary data obtained from BPS (Central Statistics Agency) Bengkulu province and DPMPTSP (Investment Service and one-stop integrated services) Bengkulu province. This research was conducted in Bengkulu province with time series data from 2011 to 2020. This research focuses on domestic and foreign investment and expenditure in the health sector and economic growth. Data processing in this study uses the eviews program. From the results of the research that has been conducted it shows that domestic investment has a positive but not significant effect on economic growth in Bengkulu province, foreign investment has a negative and insignificant effect on economic growth in Bengkulu province while spending in the health sector has a significant effect on economic growth in Bengkulu province. But together, domestic investment, foreign investment and government spending on health have no significant effect on economic growth in the province of Bengkulu.